Branding Sekolah sebagai Strategi Pengembangan Citra Institusi di Wilayah Non-Metropolitan - Eknul Khofiyah; Kaniati Amalia; Ima Widiyanah; Amrozi Khamidi; Mohammad Syahidul Haq; Karwanto Karwanto (Universitas Sarjanawiyata Tamansiswa, 2026)
Despite the growing adoption of branding practices in educational institutions, limited research has examined how public schools in non-metropolitan areas develop institutional image within socio-communal environments characterized by limited digital access. This study investigates branding management practices in SDN Pandan and SDN Warugunung Pacet, two public elementary schools located in Mojokerto Regency, Indonesia. Employing an interpretive multiple-case study with a qualitative descriptive design, the research draws on in-depth interviews, observations, and document analysis involving school principals, teachers, school committee members, and parents. Guided by the Vision–Culture–Image Alignment framework of Corporate Branding Theory, the study explores how organizational vision, culture, and stakeholder perceptions interact in shaping institutional image. The findings reveal two distinct branding pathways. SDN Pandan applies a vision-driven strategic branding model characterized by structured programs and digital communication, while SDN Warugunung Pacet adopts a community-based branding model emphasizing relational trust, cultural internalization, and word-of-mouth communication. Based on these findings, the study proposes a Dual-Pathway Branding Framework that conceptualizes strategic alignment and community authenticity as complementary mechanisms for strengthening institutional legitimacy and visibility. The study contributes to corporate branding literature by highlighting the importance of socio-communal context in non-metropolitan educational settings.